HUBUNGAN KELENTURAN PERGELANGAN TANGAN DAN KELINCAHAN DENGAN KEMAMPUAN PUKULAN FOREHAND PERMAINAN TENIS MEJA SISWA EKSTRAKURIKULER PUTRA SMPN 06 TELUK KUANTAN KECAMATAN KUANTAN TENGAH - Ony Marsah; Drs. Saripin., M.Kes AIF '; Kristi Agust., S.Pd, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is not optimal capability forehand in the game of table tennis being owned by extracurricular students at SMPN 06 Teluk Kuantan. This was due to several factors: the flexibility of the wrist and agility. Therefore, researchers want to conduct a study to prove the corelation between these variables. This type of research is double correlational. The population in this study were male students who follow in SMPN 06 Teluk Kuantan District of Kuantan Tengah extracurricular amounting to 23 people. Sample collection technique is a saturation sampling is sampling technique when all members of the population sampled. Data were obtained from the results of the test measurements wrist flexibility, agility and ability forehand. From the results of calculations known that the great value of the correlation wrist flexibility with ability forehand game of table tennis male students of SMPN 06 Kuantan Teluk District of Kuantan Tengah Extracurricular simultaneously is 0,753 at a high category. It can concluded that hypothesis (Ho) reads: There is no significant relationship between flexibility of the wrist (X1) and agility (X2) with the ability forehand game of table tennis (Y). Based on the analysis of data obtained by the correlation coefficient of r = 0, 753 with high category thus Ho is rejected and Ha accepted, so it can be concluded there is a corelation Flexibility Wrists And Agility Capabilities with Forehand ability game of Table Tennis male Students Extracurricular at SMPN 06 Teluk Kuantan District of Kuantan Central .Keywords : Wrist Flexiblity, Agility, Forehand, Table Tennis